EKSPLORASI MAKNA CINTA DALAM SYA'IR "الحب الصادق" KARYA IMAM SYAFI'I: KAJIAN HERMENEUTIKA BOUMAN - Aeni Lukviati Urbah; Allisya Rizky Islami; Aura Nasywa Azzahra, Maman Abdul Djaliel (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to reveal the meaning of true love (al-mahabbah al-ṣādiqah) in Imam Syafi'i's poem al-ḥubb al-ṣādiq through Bouman's hermeneutic approach. In the modern context marked by a crisis of values and emotional alienation, classical Islamic literature offers spiritual reflections that are relevant to the formation of ethical and humanitarian awareness. This study uses qualitative methods with literature study techniques, focusing on semantic and hermeneutic analysis of classical Arabic texts and their translations. The analysis was conducted by tracing the relationship between the author, the text, and the reader to find dynamic contextual meanings. The results of the study show that sya'ir al-ḥubb al-ṣādiq describes true love as a unity between words, actions, and moral consciousness. Imam Shafi'i emphasizes that sincere love requires obedience, gratitude, and responsibility towards the beloved. Through Bouman's framework, this text is understood not merely as a religious expression, but as a universal reflection on integrity and honesty in love. This finding enriches the study of Islamic literature and hermeneutics by offering a contextual perspective on the transcendental and humanistic value of love.